A qualitative analysis of public health officials' experience in California during COVID-19: priorities and recommendations - Rita V. Burke; Anna S. Distler; Timothy C. McCall; Timothy C. McCall; Emma Hunter; Shruti Dhapodkar; Larissa Chiari-Keith; Aaron A. Alford (Frontiers Media S.A., 2023)
ObjectivesThe aim of this study was to collect qualitative data regarding the violence faced by public health officials during the COVID-19 pandemic and create a guideline of recommendations to protect this population moving forward.MethodsTwo focus groups were conducted virtually from April 2022 to May 2022. All nine participants were public health officials from across California. A grounded theory approach was used to analyze the data from these focus groups.ResultsThe main recurrent experiences among public health officials were harassment, psychological impact, systemic backlash, and burnout. Several recommendations for supporting public health officials were highlighted, including security and protection, mental health support, public awareness, and political/institutional support.ConclusionOur study captures the violent experiences that health officials have faced during the COVID-19 pandemic. To maintain the integrity of the public health system, timely changes must be made to support and protect health officials. Our guideline of recommendations provides a multi-faceted approach to the urgent threats that officials continue to face. By implementing these solutions, we can strengthen our public health system and improve our response to future national emergencies.